In Vitro Spermatogenesis by Three-dimensional Culture of Spermatogonial Stem Cells on Decellularized Testicular Matrix: - Ashouri Movassagh, Sepideh; Banitalebi Dehkordi, Mehdi; Koruji, Morteza; Pourmand, Gholamreza; Farzaneh, Parvaneh; Ashouri Movassagh, Sanaz; Khadivi, Farnaz; Jabari, Ayob; Samadian, Azam; Abbasi, Mehdi (Galen Medical Journal, 2019)
Background: In the males, Spermatogonial Stem Cells (SSCs) contribute to the production of sex cells and fertility. In vitro SSCs culture can operate as an effective strategy for studies on spermatogenesis and male infertility treatment. Cell culture in a three-dimensional (3D) substrate, relative to a two-dimensional substrate (2D), creates better conditions for cell interaction and is closer to in vivo conditions. In the present study, in order to create a 3D matrix substrate, decellularized testicular matrix (DTM) was used to engender optimal conditions for SSCs culture and differentiation. Materials and Methods: After, testicular cells enzymatic extraction from testes of brain-dead donors, the SSCs were proliferated in a specific culture medium for four weeks, and after confirming the identity of the colonies derived from the growth of these cells, they were cultured on a layer of DTM as well as in 2D condition with a differentiated culture medium. In the Sixth week since the initiation of the differentiation culture, the expression of pre meiotic (OCT4 & PLZF), meiotic (SCP3 & BOULE) and post meiotic (CREM & Protamine-2) genes were measured in both groups. Results: The results indicated that the expression of pre meiotic, meiotic and post meiotic genes was significantly higher in the cells cultured on DTM (P ≤ 0.001). Conclusion: SSCs culture in DTM with the creation of ECM and similar conditions with in vivo can be regarded as a way of demonstrating spermatogenesis in vitro, which can be adopted as a treatment modality for male infertility. [GMJ.2019;8:e1565]